Karakteristik dan Proporsi Percobaan Bunuh Diri pada Siklus Menstruasi - Putu Kurnia Darma Pratama (Universitas Udayana, 2017)
Suicide attempt was higher two to three times in women than men. There have been allegations that the menstrual cycle hasa relationship with suicide attempts in women. This study is done to know the proportion of women who attempted suicide atfollicular, midcycle, and luteal phase at menstrual cycle and to know the characteristics of suicide attempt women patients basedon age, last educational attainment, marital status, and occupation. This study uses cross-sectional descriptive study design. Thesubjects of this study were women 11 to 50 years old who attempted suicide and comes to Bagian/SMF Psikiatri RSUP Sanglahand met the inclusion criteria. Of the 41 subjects, suicide attempt on follicular phase is 29.2%, on midcycle phase is 9.8%, andon luteal phase is 61%. The study based on the characteristics of subjects gets the result, suicide attempt women patients mostcommonly at 21-30 years old, had last educational attainment on high school, married, and working. From the result of this study,suicide attempt occur most commonly in women who were at luteal phase of menstrual cycle. With these results, this studyexpected can be used as a basis for further research that would later be useful in the prevention and control in women who areat risk for suicide attempt.